Cilostazol Versus Aspirin on White Matter Changes in Cerebral Small Vessel Disease: A Randomized Controlled Trial. Issue 3 (March 2022) - Kim, Byeong C.; Youn, Young Chul; Jeong, Jee Hyang; Han, Hyun Jeong; Kim, Jong Hun; Lee, Jae-Hong; Park, Kee Hyung; Park, Kyung Won; Kim, Eun-Joo; Oh, Mi Sun; Shim, YongSoo; Lee, Jong-Min; et al.
Abstract : Background and Purpose: Cerebral small vessel disease is characterized by progressive cerebral white matter changes (WMCs). This study aimed to compare the effects of cilostazol and aspirin on changes in WMC volume in patients with cerebral small vessel disease. Methods: In a multicenter, double-blind, randomized controlled trial, participants with moderate or severe WMCs and at least one lacunar infarction detected on brain magnetic resonance imaging were randomly assigned to the cilostazol and aspirin groups in a 1:1 ratio. Cilostazol slow release (200 mg) or aspirin (100 mg) capsules were administered once daily for 2 years. The primary outcome was the change in WMC volume on magnetic resonance images from baseline to 2 years. Secondary imaging outcomes include changes in the number of lacunes or cerebral microbleeds, fractional anisotropy, and mean diffusivity on diffusion tensor images, and brain atrophy. Secondary clinical outcomes include all ischemic strokes, all ischemic vascular events, and changes in cognition, motor function, mood, urinary symptoms, and disability. Results: Between July 2013 and August 2016, 256 participants were randomly assigned to the cilostazol (n=127) and aspirin (n=129) groups. Over 2 years, the percentage of WMC volume to total WM volume and the percentage of WMC volume to intracranial volume increased in both groups, but neither analysis showed significant differences between the groups. The peak height of the mean diffusivity histogram in normal-appearing WMs was significantly reduced in the aspirin group compared with the cilostazol group. Cilostazol significantly reduced the risk of ischemic vascular event compared with aspirin (0.5 versus 4.5 cases per 100 person-years; hazard ratio, 0.11 [95% CI, 0.02–0.89]). Conclusions: There was no significant difference between the effects of cilostazol and aspirin on WMC progression in patients with cerebral small vessel disease. Registration: URL: https://www.clinicaltrials.gov ; Unique identifier: NCT01932203. Abstract : Supplemental Digital Content is available in the text.